2019
DOI: 10.1242/jcs.233486
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ-induced fibroblast activation requires persistent and targeted HDAC-mediated gene repression

Abstract: Tissue fibrosis is a chronic disease driven by persistent fibroblast activation that has recently been linked to epigenetic modifications. Here, we screened a small library of epigenetic small-molecule modulators to identify compounds capable of inhibiting or reversing TGFβ-mediated fibroblast activation. We identified pracinostat, an HDAC inhibitor, as a potent attenuator of lung fibroblast activation and confirmed its efficacy in patient-derived fibroblasts isolated from fibrotic lung tissue. Mechanistically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 99 publications
9
63
0
1
Order By: Relevance
“…Finally, in order to confirm the proper functionality and the suitability to use 10-4A BFP cells in high throughput assays, we performed plate-reader based experiments to analyze the dose- and time-response of Acta2 expression (i.e., myofibroblast induction) in response to exposure to distinct profibrotic cytokines. The effective concentrations were in agreement with previous reports for induction of fibrosis ( Saito et al, 2003 ; Yanaba et al, 2011 ; Datta et al, 2013 ; Lee et al, 2017 ; Jones et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…Finally, in order to confirm the proper functionality and the suitability to use 10-4A BFP cells in high throughput assays, we performed plate-reader based experiments to analyze the dose- and time-response of Acta2 expression (i.e., myofibroblast induction) in response to exposure to distinct profibrotic cytokines. The effective concentrations were in agreement with previous reports for induction of fibrosis ( Saito et al, 2003 ; Yanaba et al, 2011 ; Datta et al, 2013 ; Lee et al, 2017 ; Jones et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…RNA sequencing analysis from recent work on lung fibroblasts helped us to corroborate our results (Fig. 5G) (Jones et al, 2019). The pan HDAC inhibitor, pracinostat, attenuates TGF-β-induced repression of Tcf7l2 gene expression (Fig.…”
Section: Resultssupporting
confidence: 78%
“…5C,D). Based on recent findings that demonstrated that TGFβ-mediated fibroblast activation requires HDAC-mediated transcriptional repression (Jones et al, 2019), we examined whether inhibiting HDACs with TSA may modify TGF-β-mediated reduction of TCF7L2 expression. we examined whether inhibiting HDACs with TSA may alter TCF7L2 expression in response to TGF-β signaling.…”
Section: Resultsmentioning
confidence: 99%
“…S3H). Furthermore, RNA-seq analyses of TGF-β-treated idiopathic pulmonary fibrosis (IPF) lung (Jones et al, 2019) and cardiac fibroblasts (Schafer et al, 2017) show that TGF-β1 alters the expression of several validated target genes of the Wnt/β-Catenin/ TCF7L2 pathway. Dkk1, Dkk3, Lrp5, Lef1, Tcf7l1, Tgfbr2, Ctbp2, Sox9, Cxcl12 and Nfatc4 expression is reduced, whereas expression of the Fn1, Col1a1, Ctgf, Tgfb1, Foxo1, Wnt5a, Wnt5b, Wnt11, Wnt9a, Myc, and Oat TCF7L2-target genes is increased after TGF-β1 treatment (Fig.…”
Section: Tgf-β Signaling Downregulates the Expression Of Tcf7l2 In Pdmentioning
confidence: 99%
“…5C,D). Based on recent findings that demonstrated that TGFβ-mediated fibroblast activation requires HDAC-mediated transcriptional repression (Jones et al, 2019), we examined whether inhibiting HDACs with TSA modified the TGF-β-mediated reduction of TCF7L2 expression. Therefore, cells were treated with TGF-β1 and/or TSA for 8 h and then TCF7L2 protein levels were evaluated by western blotting.…”
Section: Tgf-β Requires Hdac Activity To Repress Tcf7l2 Expressionmentioning
confidence: 99%